Effects of work in childhood on health in the opinion of respondents from agricultural families - Stanisław Lachowski; Magdalena Florek-Łuszczki (Nofer Institute of Occupational Medicine, 2013)
Background: The engagement of children in work is common in agricultural families. Work of children brings about specific benefits to both the family and the children; however, at the same time, it creates many hazards, including health risk. Materials and Method: The aim of the study was to determine current and delayed health effects among individuals who were engaged in agricultural activities in childhood. The study was conducted using the method of diagnostic survey questionnaire and covered a group of 482 adults from agricultural families. Results: The majority of respondents expressed the opinion that work in childhood had no impact on their health. At the same time, 2/5 of respondents considered that work on their parents' farm exerted an effect on their health in childhood (current effects), whereas nearly 1/3 admitted that an engagement in work in childhood also affected their present state of health (delayed effects). In the respondents' opinion, overloading with work in childhood exerted an adverse effect on their health, and also resulted in health problems in adulthood. Conclusion: The engagement of children in agricultural work in a small amount of working time, and adjustment of assigned jobs to their capabilities brings about many health benefits with low health risk. In turn, the engagement of children in work from their youngest years and overloading them with work exerts an adverse effect on health, especially in later life. Med Pr 2013;64(3):373-385